Epistemologies of Biomedical Ethics: A Tribute to Dr. Engelhardt - Cutter, Mary Ann G. (Conatus - Journal of Philosophy, 2018)
In this essay, and in his honor, I focus on two of physician-philosopher H. Tristram Engelhardt, Jr.’s many contributions, namely, his view that biomedical ethics (1) cannot offer a singular content-driven theoretical approach and (2) requires an appreciation of epistemologies of knowing in medicine. While these two positions remain controversial, because we all want definitive answers to our questions concerning what we ought to do in medicine and elsewhere, Dr. Engelhardt’s view makes possible discussion and debate in medicine to include diverse, defensible ways of knowing. In the end, Dr. Engelhardt’s approach in biomedical ethics is one of shared decision making and negotiation. This is an important model if we take respect for patients seriously in the clinical setting.